LITERATURE REVIEW: ASSOCIATION BETWEEN BULLOUS PEMPHIGOID AND IMMUNIZATION IN INFANTS - Majidah, Eninta Karyana (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: Bullous pemphigoid (BP), is the most common autoimmune bullous disease and mostly affects the elderly, but is rare in the pediatric population. The etiology is still unknown. In particular, maternal antibodies and foreign antigens such as drugs, infections, and vaccines are thought to trigger BP in childhood. Purpose: To review the literature bullous pemphigoid and immunization in infants. Review: Approximately 110 reports of BP in childhood, including 21 reports occurred after childhood vaccination. In each case, a short latency period was described from vaccination to clinical manifestation with most cases occurring within a week (range: 5 hours – 4 weeks). This supports the existence of a relationship between vaccination and clinical symptoms of BP, recurrence of BP symptoms along with exposure to vaccination, as well as the high incidence of vaccine-related BP in infants. This is supported by the temporal relationship between vaccination and the onset of lesions as well as the observation of recurrence after administration of a new dose. However, on the other hand, the low incidence of infantile BP in widely vaccinated populations suggests that the association may be only incidental. Conclusion: Vaccination clearly has a relationship with the occurrence of bullous pemphigoid in infants. Vaccination may activate the immune system, but the pathogenesis of how vaccines trigger BP is still unknown.